Inactivation of Cys674 in SERCA2 increases BP by inducing endoplasmic reticulum stress and soluble epoxide hydrolase. (30th January 2020) - Liu, Gang; Wu, Fuhua; Jiang, Xiaoli; Que, Yumei; Qin, Zhexue; Hu, Pingping; Lee, Kin Sing Stephen; Yang, Jian; Zeng, Chunyu; Hammock, Bruce D.; Tong, Xiaoyong
Abstract : Background and Purpose: The kidney is essential in regulating sodium homeostasis and BP. The irreversible oxidation of Cys 674 (C674) in the sarcoplasmic/endoplasmic reticulum calcium ATPase 2 (SERCA2) is increased in the renal cortex of hypertensive mice. Whether inactivation of C674 promotes hypertension is unclear. Here we have investigated the effects on BP of the inactivation of C674, and its role in the kidney. Experimental Approach: We used heterozygous SERCA2 C674S knock‐in (SKI) mice, where half of C674 was substituted by serine, to represent partial irreversible oxidation of C674. The BP, urine volume, and urine composition of SKI mice and their littermate wild‐type (WT) mice were measured. The kidneys were collected for cell culture, Na + /K + ‐ATPase activity, protein expression, and immunohistological analysis. Key Results: Compared with WT mice, SKI mice had higher BP, lower urine volume and sodium excretion, up‐regulated endoplasmic reticulum (ER) stress markers and soluble epoxide hydrolase (sEH), and down‐regulated dopamine D1 receptors in renal cortex and cells from renal proximal tubule. ER stress and sEH were mutually regulated, and both upstream of D1 receptors. Inhibition of ER stress or sEH up‐regulated expression of D1 receptors, decreased the activity of Na + /K + ‐ATPase, increased sodium excretion, and lowered BP in SKI mice. Conclusions and Implications: The inactivation of SERCA2 C674 promotes the development of hypertension by inducing ER stress and sEH. Our study highlights the importance of C674 redox status in BP control and the contribution of SERCA2 to sodium homeostasis and BP in the kidney.